Exploring Anger Among Offenders: The Role of Emotion Dysregulation and Alexithymia. Issue 1 (2nd January 2017) - Velotti, Patrizia; Garofalo, Carlo; Callea, Antonino; Bucks, Romola S.; Roberton, Terri; Daffern, Michael
Abstract : This study tests whether specific dimensions of emotion dysregulation predict maladaptive anger expression among offenders from Italy and Australia. In particular, it examines the unique associations among emotion dysregulation dimensions and different aspects of anger expression and control, in both inmates and offenders on parole. Multiple regression analyses reveal that difficulties controlling impulsive behaviour when distressed are related to state anger, trait anger, and chronic anger expression. On the other hand, alexithymia predicts the maladaptive expression of anger inwardly directed. Finally, lack of emotional awareness and limited access to emotion regulation (ER) strategies are negatively related to anger control, suggesting that they may represent useful treatment targets. Interestingly, incarcerated offenders reported significantly higher levels of state anger and lower levels of anger control out (i.e. seeking support from others) than offenders living on parole in the community, highlighting the importance of contextual influences in the emotional life of offenders.